APPLICATION OF THE PHOTOHYDROMETRIC METHOD FOR DETERMINING WATER DISCHARGE IN MOUNTAIN RIVERS (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
This article examines the results of testing a photohydrometric method by large-scale particle-image velocimetry (LSPIV) for determining water discharge over a wide range of flow velocity variations on mountain rivers in the Kuban Basin. The aim of the study is to evaluate the applicability of the proposed technology as an accessible, non-intrusive, and labor-efficient tool for continuous hydrological monitoring of mountain river discharge. During the testing of this method, water discharge was measured using both a current meter and LSPIV. The authors developed an algorithm for assessing the quality of measurement, based on a comparative statistical and graphical analysis of surface flow velocity fields. Additionally, a study of empirical distributions of flow velocities by flow depth is conducted, and their generalized numerical estimates are provided. Conclusions are drawn regarding the specific application of the LSPIV, and recommendations are provided for determining water discharge on mountain rivers using this method.
Keywords: LSPIV; water discharge; surface velocity; mountain streams; turbulence; flow assessment